Ascribing dimensions enhancing employee innovation: function of job characteristics, psychological capital (PsyCap), work-based learning (WBL) and inventive environment - Aleen, Lamiza (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.